2015
DOI: 10.1080/15226514.2015.1058331
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation potential ofLemna minorL. for heavy metals

Abstract: Phytoremediation potential of L. minor for cadmium (Cd), copper (Cu), lead (Pb), and nickel (Ni) from two different types of effluent in raw form was evaluated in a glass house experiment using hydroponic studies for a period of 31 days. Heavy metals concentration in water and plant sample was analyzed at 3, 10, 17, 24, and 31 day. Removal efficiency, metal uptake and bio-concentration factor were also calculated. Effluents were initially analyzed for physical, chemical and microbiological parameters and resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(47 citation statements)
references
References 35 publications
3
30
1
3
Order By: Relevance
“…In contrast, the concentration of lead in the current study was slightly higher than the values reported for gray water [29]. Deterioration of sewerage pipelines and the wear of household plumbing fixtures are considered important sources of Co in domestic wastewater [23,34]. Concentrations of Co, Cd, Fe, Mn and to some extent Cu in the present study were higher than the allowable limit for irrigation.…”
Section: Salinity and Heavy Metal Contents Of The Wastewatercontrasting
confidence: 54%
“…In contrast, the concentration of lead in the current study was slightly higher than the values reported for gray water [29]. Deterioration of sewerage pipelines and the wear of household plumbing fixtures are considered important sources of Co in domestic wastewater [23,34]. Concentrations of Co, Cd, Fe, Mn and to some extent Cu in the present study were higher than the allowable limit for irrigation.…”
Section: Salinity and Heavy Metal Contents Of The Wastewatercontrasting
confidence: 54%
“…Similar results were obtained for E. Crassipes with 3 to 15 time more concentration in roots [13,18]. Due to industrial effluent, accumulation of various metal ions and external disturbance might affect the accumulation capacity of the plant [10,12,19].…”
Section: Discussionsupporting
confidence: 81%
“…Phytoremediation of heavy metals with aquatic plants has gained significant consideration due to its elegance and cost-effectiveness [39,227]. The earlier worker has demonstrated that aquatic plants have the capability to eliminate HMs from different kinds of wastewater [140,225,245,246].…”
Section: Significance Of Aquatic Plants For Phytoremediation Of Wastementioning
confidence: 99%